Evaluation of Traffic Accident-Prone Points on Haji Rais Abdul Rachman–Hasanuddin Road Section, Pontianak City - Nur Haida, Khansa Putri; Kadarini, Siti Nurlayli; Sumiyattinah (Rekayasa Sipil, 2026)
Rapid urban development in Pontianak City has led to an increase in traffic volume, resulting in congestion, road damage, and heightened accident risks. This study identifies accident-prone points along the Haji Rais A. Rachman–Hasanuddin Road section, analyzes accident patterns and contributing factors, and proposes targeted safety improvements. Using accident data from 2019 to 2023 and field surveys that assessed road conditions and traffic, accident severity was quantified using the Equivalent Accident Number (EAN), and accident clusters were identified using the Upper Control Limit (UCL) method. The findings reveal that driver-related factors, particularly motorcycle use, are the primary causes of accidents, with peak occurrences near shopping areas during the morning hours. Segments 3 and 4 emerged as critical black spots requiring intervention. Recommended measures include enhanced law enforcement, improved road markings, and addressing uneven road sections to reduce the incidence of accidents. This study fills a gap in applying rigorous statistical methods in medium-sized Indonesian cities, offering evidence-based recommendations for local policymakers to improve urban traffic safety